Sequencing Analysis of NS3/4A, NS5A, and NS5B Genes from Patients Infected with Hepatitis C Virus Genotypes 5 and 6 - Ku, Karin S. (J Clin Microbiol, 2016)
Direct-acting antivirals (DAAs) with activity against multiple genotypes of the hepatitis C virus (HCV) were recently developed and approved for standard-of-care treatment. However, sequencing assays to support HCV genotype 5 and 6 analysis are not widely available. Here, we describe the development of a sequencing assay for the NS3/4A, NS5A, and NS5B genes from HCV genotype 5 and 6 patient isolates. Genotype- and subtype-specific primers were designed to target NS3/4A, NS5A, and NS5B for cDNA synthesis and nested PCR amplification. Amplification was successfully performed for a panel of 32 plasma samples from HCV-infected genotype 5 and 6 patients with sequencing data obtained for all attempted samples. LiPA 2.0 (Versant HCV genotype 2.0) is a reverse hybridization line probe assay that is commonly used for genotyping HCV-infected patients enrolled in clinical studies. Using NS3/4A, NS5A, and NS5B consensus sequences, HCV subtypes were determined that were not available for the initial LiPA 2.0 result for genotype 6 samples. Samples amplified here included the following HCV subtypes: 5a, 6a, 6e, 6f, 6j, 6i, 6l, 6n, 6o, and 6p. The sequencing data generated allowed for the determination of the presence of variants at amino acid positions previously characterized as associated with resistance to DAAs. The simple and robust sequencing assay for genotypes 5 and 6 presented here may lead to a better understanding of HCV genetic diversity and prevalence of resistance-associated variants.